The answer is (4x+3) (x^2+2)
Whole numbers, integers, fractions, terminating decimals and repeating decimals are all rational numbers.
Answer:
Step-by-step explanation:
a² - b² = (a+ b)(a - b)
1) (2n-4/2n) ÷ (n^2-4/n)
![=\frac{2n-4}{2n}*\frac{n}{n^{2}-4}\\\\=\frac{2n-2*2}{2n}*\frac{n}{n^{2}-2^{2}}\\\\=\frac{2*(n-2)}{2n}*\frac{n}{(n+2)*(n-2)}\\\\=\frac{1}{n+2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2n-4%7D%7B2n%7D%2A%5Cfrac%7Bn%7D%7Bn%5E%7B2%7D-4%7D%5C%5C%5C%5C%3D%5Cfrac%7B2n-2%2A2%7D%7B2n%7D%2A%5Cfrac%7Bn%7D%7Bn%5E%7B2%7D-2%5E%7B2%7D%7D%5C%5C%5C%5C%3D%5Cfrac%7B2%2A%28n-2%29%7D%7B2n%7D%2A%5Cfrac%7Bn%7D%7B%28n%2B2%29%2A%28n-2%29%7D%5C%5C%5C%5C%3D%5Cfrac%7B1%7D%7Bn%2B2%7D)
2) [y^2-36/y^2-49] ÷[ y+6/y-7]
![=\frac{y^{2}-36}{y^{2}-49}*\frac{y-7}{y+6}\\\\=\frac{y^{2}-6^{2}}{y^{2}-7^{2}}*\frac{y-7}{y+6}\\\\=\frac{(y+6)*(y-6)}{(y+7)*(y-7)}*\frac{y-7}{y+6}\\\\=\frac{y-6}{y+7}\\](https://tex.z-dn.net/?f=%3D%5Cfrac%7By%5E%7B2%7D-36%7D%7By%5E%7B2%7D-49%7D%2A%5Cfrac%7By-7%7D%7By%2B6%7D%5C%5C%5C%5C%3D%5Cfrac%7By%5E%7B2%7D-6%5E%7B2%7D%7D%7By%5E%7B2%7D-7%5E%7B2%7D%7D%2A%5Cfrac%7By-7%7D%7By%2B6%7D%5C%5C%5C%5C%3D%5Cfrac%7B%28y%2B6%29%2A%28y-6%29%7D%7B%28y%2B7%29%2A%28y-7%29%7D%2A%5Cfrac%7By-7%7D%7By%2B6%7D%5C%5C%5C%5C%3D%5Cfrac%7By-6%7D%7By%2B7%7D%5C%5C)
3) [m^2-1/ m^2-m] ÷ [m^2-7m-8/3m
]
![=\frac{m^{2}-1}{m^{2}-m}*\frac{3m}{m^{2}-7m-8}\\\\=\frac{(m+1)*(m-1)}{m*(m-1)}*\frac{3m}{(m-8)*(m+1)}\\\\=\frac{3}{m-8}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bm%5E%7B2%7D-1%7D%7Bm%5E%7B2%7D-m%7D%2A%5Cfrac%7B3m%7D%7Bm%5E%7B2%7D-7m-8%7D%5C%5C%5C%5C%3D%5Cfrac%7B%28m%2B1%29%2A%28m-1%29%7D%7Bm%2A%28m-1%29%7D%2A%5Cfrac%7B3m%7D%7B%28m-8%29%2A%28m%2B1%29%7D%5C%5C%5C%5C%3D%5Cfrac%7B3%7D%7Bm-8%7D)
Hint : m² - 7m - 8
sum = -7
Product = -8
Factor = (-8), 1
m² - 7m - 8 =m² - 8m + m - 8
= m*(m - 8) + (m-8)
= (m - 8)(m +1)
Step-by-step explanation:
xy + 10 = 0. => y = -10/x.
2x + 3y = 7. => 3y = -2x + 7, y = -2/3 x + 7/3.
When -10/x = -2/3 x + 7/3,
-10 = -2/3 x² + 7/3 x, 2/3 x² - 7/3 x - 10 = 0.
=> 2x² - 7x - 30 = 0
=> (2x + 5)(x - 6) = 0
=> x = -2.5 or x = 6.
dy/dx = d/dx [-10/x] = 10/x².
When x = -2.5, dy/dx = 10 / (-2.5)² = 1.6.
When x = 6, dy/dx = 10 / (6)² = 5/18.
Hence the gradients at the points are 1.6 and 5/18.
The answer is 32x^4-24x^3+40x^2-36x-12